Hematological parameters and antioxidant responses in olive flounder Paralichthys olivaceus in biofloc depend on water temperature. (May 2019) - Kim, Jun-Hwan; Kim, Su Kyoung; Hur, Young Baek
Abstract: The purpose of this study was to ascertain the optimum water temperature for breeding juvenile Paralichthys olivaceus in biofloc. Hemoglobin and hematocrit were significantly decreased when the temperature was higher than 28 °C. Plasma calcium, glucose, cholesterol, glutamic-oxaloacetic transaminase, and glutamic pyruvic transaminase were significantly elevated at high temperatures, whereas total protein was substantially lower. Superoxide dismutase and glutathione-S-transferase activities in the liver and gills were significantly elevated at high temperatures, whereas glutathione was significantly lower. This indicates that temperatures greater than 26 °C induced hematological changes and oxidative stress in the juvenile P. olivaceus in biofloc. We ascribe these changes to thermal stress. Highlights: High water temperature affected the hematological parameters of the flounder raised in biofloc. Antioxidant responses were significantly changed by high water temperature. High water temperature to P. olivaceus affected as thermal stress.